α-Functionalization of the Carbonyl Group for the Construction of Pyrazoline Rings Derived from 1,3-Indandione - Ali, Raniah T.; Dawood, Rafid S. (Iraqi Journal of Science, 2024)
This work includes the synthesis of new pyrazoline derivatives 5-13 over three steps starting from 1,3-indandione. The first step included the acylation of 1,3- indandione with acetyl chloride to produce compound 1 with excellent yield (90%). In the second step, the enolate form of 1 was condensed with various aromatic aldehydes (benzaldehyde, p-nitrobenzaldehyde, and p chlorobenzaldehyde) to afford the corresponding α,β-unsaturated carbonyl derivatives 2-4 in high yields (93-95%). The third step involved a reaction of 2-4 with hydrazine hydrate, phenyl hydrazine, and p-nitrophenyl hydrazine to give the desired pyrazoline derivatives 5-13 in yields ranging from 70 to 83%. The structure of the synthesized compounds was verified through FT-IR and 1H NMR spectroscopy. Additionally, a subset of the synthesized compounds underwent testing to evaluate their antibacterial and antioxidantproperties.